Censos y cartografía de Quito y su área metropolitana (1573-2022): búsqueda, tratamiento y representación geográfica (Debates) - Godard, Henri (2025)
This article presents the initial progress made in creating a geohistorical database of Quito, comprising city maps dating back to 1573 and population censuses since 1982. The aim is to supplement the information produced and systematized by the Quito Computerized Atlas Research Program (1984- 1992). It describes the process of collecting information in its historical and scientific contexts; it examines the maps, composed of several layers, and their potential uses for research and professional work; and it presents some preliminary analyses derived from the processing of the database.